Reformulation of Restorative Justice for Negligent Offenses in the Indonesian Criminal Law System - Muhammad Ali; Mispansyah Mispansyah; Diana Haiti (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, negligence offenses lacking malicious intent should be resolved through a restorative approach emphasizing victim recovery and offender reintegration. However, in reality, negligence cases remain dominated by imprisonment and lack comprehensive mechanisms. This research aims to analyze philosophical foundations of restorative justice, evaluate its implementation in the Indonesian criminal justice system, and formulate an ideal legal reformulation model. The method used is normative legal research with statutory, conceptual, and comparative approaches, analyzing primary, secondary, and tertiary legal materials qualitatively-prescriptively. The findings show that restorative justice has a strong philosophical foundation for negligence offenses, supported by justice theory, reintegrative theory, concept of balancing legal values, as well as Pancasila and progressive legal values. However, its implementation is hindered by regulatory fragmentation across law enforcement institutions and absence of clear normative parameters. This research offers a contribution in the form of a Substantive Justice-Based Restorative Justice Reformulation Model built on three foundations and four cumulative normative requirements, expected to bridge the gap between the need for a restorative approach and the availability of an adequate normative framework.